If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + -3(n + -2) + -8 + n = 0 Reorder the terms: 6n + -3(-2 + n) + -8 + n = 0 6n + (-2 * -3 + n * -3) + -8 + n = 0 6n + (6 + -3n) + -8 + n = 0 Reorder the terms: 6 + -8 + 6n + -3n + n = 0 Combine like terms: 6 + -8 = -2 -2 + 6n + -3n + n = 0 Combine like terms: 6n + -3n = 3n -2 + 3n + n = 0 Combine like terms: 3n + n = 4n -2 + 4n = 0 Solving -2 + 4n = 0 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 4n = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 4n = 0 + 2 4n = 0 + 2 Combine like terms: 0 + 2 = 2 4n = 2 Divide each side by '4'. n = 0.5 Simplifying n = 0.5
| -2x^5-12x^2+30x+200=0 | | 16(2x-5)=-2(5x-18) | | 9y+4=33 | | 8m+8m+m+m=36 | | (2x+3)=180 | | 20x+4+6x+4=8x+18 | | h=-16t^2+18t+10 | | 2x+2=2-5(-4-5) | | -23=8w+9 | | 4(x+2)-8=22 | | 5(2x+3)=3(3x+7) | | 6x+8=4(x+17) | | 22-2h=-32 | | -0.3-m=-0.1m+0.37-0.3m | | -6t+2(r+2)-5=-20 | | 3.5v=8+7.5v-4 | | 5.4h+5=9h | | 16(n+12)=4n | | (2x-11)+(2x+27)+3x=180 | | 5z^2=80 | | 4x-15=11+4x | | 3x+84+2x+5=180 | | 3y=11-2x | | 7+3p=-26 | | 1-6(q+2)=-23 | | 4x+84+2x+5=180 | | 0.3x-0.14x=4 | | 4w^2+w-95=0 | | 5.32y+3y=1 | | -6*-64= | | 7x+3=57+x | | 360=40(x-1) |